Post-Truth and the Epistemological Crisis: Reconstructing Truth in the Evolving Landscape of Social Media - Arrasyid; Taufiqurrahman; Sarwan; Widia Fithri; Rido Putra (Insaniyat: Journal of Islam and Humanities, 2025)
The rapid expansion of digital media and the surge of misinformation have created a profound epistemological crisis that challenges established notions of truth and knowledge. This study analyzes the reconstruction of truth in the post-truth era, in which emotional narratives and ideological biases frequently outweigh empirical evidence. Employing a descriptive-analytical method, the research explores the implications of post-truth dynamics for epistemic authority, public trust, and digital literacy. Primary and secondary sources including academic literature, books, and peer-reviewed articles on epistemology and digital media are examined to provide a comprehensive theoretical framework. The findings indicate that misinformation is often fueled by emotional persuasion, algorithmic personalization intensifies ideological polarization, and diminishing institutional credibility accelerates epistemic relativism. These conditions collectively weaken society’s capacity to distinguish reliable information from falsehoods. The study concludes that reconstructing truth in the digital age requires a multidimensional strategy that integrates robust digital literacy, transparent media practices, and strengthened epistemic responsibility. Such an approach is essential to restoring informed judgment, rebuilding trust, and safeguarding the integrity of knowledge in contemporary public discourse.